Prediction of Familial Hypercholesterolemia in Patients at High Atherosclerotic Cardiovascular Disease Risk Using a Recently Validated Algorithm - Latifah Alothman, MD; Magdaline Zawadka, MD; Sumayah Aljenedil, MD; Mahesh Kajil, MD; David Bewick, MD; Daniel Gaudet, MD, PhD; Robert A. Hegele, MD; Eva Lonn, MD, MSc; Daniel Ngui, MD; Isabelle Ruel, PhD; Michelle Tsigoulis, RN; Narendra Singh, MD; et al. (CJC Open, 2019)
Background: The prevalence of heterozygous familial hypercholesterolemia (FH) is 1 of 250 in the general population and approximately 1 of 125 in patients with atherosclerotic cardiovascular disease (ASCVD), yet only a minority are diagnosed. The diagnostic criteria for FH rely on a point system using low-density lipoprotein cholesterol (LDL-C), family history, cutaneous manifestations, and molecular diagnosis. The aim of the present study was to determine the prevalence of FH in the Relating Evidence to Achieve Cholesterol Targets (REACT) registry. Methods: Patients were enrolled as ASCVD (n = 86) or FH (n = 109) and with an LDL-C level > 3.0 mmol/L despite maximally tolerated statin therapy. FH was diagnosed clinically using a validated clinical application integrating an imputation for baseline (untreated) LDL-C levels. Results: There were 109 men and 86 women with a mean age of 63 ± 12 years. Diabetes (29.7%), hypertension (62.1%), smoking (37.9%), and family history of premature ASCVD (59.5%) were common. On-treatment LDL-C was 4.26 ± 0.94 mmol/L. On the basis of the dose and type of statin ± ezetimibe, imputed baseline LDL-C was 7.04 ± 2.90 mmol/L. A diagnosis of probable/definite FH was found in 54.7%, 49.5%, and 61.5% of patients according to the Simon Broome, Dutch Lipid Clinic Network criteria, and the new Canadian FH definition, respectively. Of note, 40% of patients in the ASCVD inclusion subgroup had probable or definite FH. Conclusions: Our study reveals that a substantial proportion of patients with ASCVD whose LDL-C levels are > 3.0 mmol/L despite maximally tolerated statins have heterozygous FH. Clinicians should consider using the recently described algorithm to assess the possibility of FH in this high-risk population. Résumé: Contexte: La prévalence de l’hypercholestérolémie familiale (HF) hétérozygote est de 1 cas sur 250 dans la population générale et d’environ 1 cas sur 125 chez les patients atteints d’une maladie cardiovasculaire athérosclérotique (MCVAS), pourtant on ne la diagnostique que dans une minorité de cas. Les critères diagnostiques de l’HF reposent sur un système de points utilisant comme paramètres le cholestérol à lipoprotéines de faible densité (C-LDL), les antécédents familiaux, les manifestations cutanées et le diagnostic moléculaire. La présente étude visait à déterminer la prévalence de l’HF parmi les patients répertoriés dans le registre REACT (Relating Evidence to Achieve Cholesterol Targets). Méthodologie: Les patients admis à l’étude étaient considérés comme étant atteints d’une MCVAS (n = 86) ou d’une HF (n = 109) et présentaient un taux de C-LDL > 3,0 mmol/l malgré la prise d’un traitement par statine à la dose maximale tolérée. L’HF a été diagnostiquée sur le plan clinique à l’aide d’une application clinique validée incluant une imputation des taux de C-LDL initiaux (en l’absence de traitement). Résultats: L’étude comptait 86 femmes et 109 hommes âgés en moyenne de 63 ± 12 ans. Le diabète (29,7 %), l’hypertension (62,1 %), le tabagisme (37,9 %) et les antécédents familiaux de MCVAS prématurée (59,5 %) étaient fréquents. Sous traitement, le taux de C-LDL était de 4,26 ± 0,94 mmol/l. D’après la dose et le type de statine ± ézétimibe administrés, le taux de C-LDL imputé au départ était de 7,04 ± 2,90 mmol/l. Un diagnostic d’HF probable ou certaine a été établi respectivement chez 54,7 %, 49,5 % et 61,5 % des patients selon les critères de Simon Broome et du Dutch Lipid Clinic Network, ainsi que la nouvelle définition canadienne de l’HF. Notons que 40 % des patients dans le sous-groupe d’inclusion de la MCVAS présentaient une HF probable ou certaine. Conclusions: Notre étude révèle qu’une proportion importante de patients atteints de MCVAS dont les taux de C-LDL sont > 3,0 mmol/l malgré la prise de statines à la dose maximale tolérée présentent une HF hétérozygote. Les cliniciens devraient envisager d’utiliser l’algorithme récemment décrit pour évaluer la présence possible d’une HF dans cette population à haut risque.